1975
DOI: 10.1530/jrf.0.0440461
|View full text |Cite
|
Sign up to set email alerts
|

Possible Mechanisms of Cadmium Fetotoxicity in Golden Hamsters and Mice: Uptake by the Embryo, Placenta and Ovary

Abstract: Summary. Pregnant golden hamsters and mice of different gestational ages were injected intravenously with 109CdCl2. The whole animal or the uterus and embryos were submitted to autoradiography. Cadmium administered on the 8th day accumulated in the primitive gut of the embryos. No cadmium was detected in the embryos after administration on or after the 9th day (hamster) and 11th day (mouse). This finding can be explained by the ability of cadmium to pass from the yolk-sac cavity into the primitive gut (where i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
1

Year Published

1981
1981
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(24 citation statements)
references
References 26 publications
(31 reference statements)
2
21
0
1
Order By: Relevance
“…These findings are consistent with those of earlier studies which showed that susceptibility to the teratogenic effects of cadmium and other extraneous factors varies with the developmental stage at the time of exposure (Chiquoine 1965;Ferm 1971;Barr 1973;Gale and Ferm 1973;Wo1kowski 1974;Hall 1977). The rate of uptake and accumulation of cadmium in embryonic, placental, and ovarian tissues also depends on the day of pregnancy on which the metal is administered (Dencker 1975).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…These findings are consistent with those of earlier studies which showed that susceptibility to the teratogenic effects of cadmium and other extraneous factors varies with the developmental stage at the time of exposure (Chiquoine 1965;Ferm 1971;Barr 1973;Gale and Ferm 1973;Wo1kowski 1974;Hall 1977). The rate of uptake and accumulation of cadmium in embryonic, placental, and ovarian tissues also depends on the day of pregnancy on which the metal is administered (Dencker 1975).…”
Section: Discussionsupporting
confidence: 91%
“…It is unlikely, therefore, that changes in progesterone and oestrogen production by the ovary following treatment with cadmium are responsible to any great extent for the foetal malformations observed in the present study. However, cadmium does accumulate in the ovary (Dencker 1975) and can decrease the activity (Unger and Clausen 1973) of cytochrome P-450 which is involved in steroid biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations